Design of Curriculum Matrix for Robotics Education Derived from Bloom's Taxonomy and Educational Curriculum of 2013 - Binugroho, Eko Henfri; Suryawati Ningrum, Endah; Kurnia Basuki, Dwi; Rachmat Anom Besari, Adnan (IPTEK Journal of Proceedings Series, 2014)
Even though robotics have gaining an attention from students of every educational level since elementary school up to higher education, their impact in student’s education itself is still relatively small. Most of the robotics competitions in Indonesia are still focus on the result but not in the process. This paper presents an educational matrix of curriculum based on robotics which focused on the process and learning outcomes of the education. The proposed Curriculum Matrix is derived from Bloom's Taxonomy which synchronized with the Educational Curriculum of 2013 from the Indonesian Ministry of Education and Culture. Hereafter, the activities of education are designed based the available robotics module together with the designed Curriculum Matrix. By using the Curriculum Matrix, the proportion of education activities can be evaluated to achieve the learning outcomes for the specified educational level more easily